Fair Trade Certification and Its Influence on International Markets - Porhomovici, Kateřina; Shymanska, Kateryna; Agustina, Shirley Basauli; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This bachelor's thesis introduces the Fairtrade International certification system and examines the causes behind the unequal distribution of trade benefits, as well as how Fairtrade seeks to address these issues. It explores both the advantages of Fairtrade certification and its common criticisms. Drawing on case studies from three key regions (Latin America, Africa, and Asia), the thesis analyzes data to assess the actual impact of Fairtrade certification. In conclusion, it offers recommendations for improving the certification system to enhance its effectiveness.
Vedoucí práce: Kateryna Shymanska
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses